The impact of customer perceived innovativeness on customer happiness and revisit intention through customer value co-creation behaviors in quick-service restaurants - Amer, Sally Mohamed (International Journal of Innovative Research and Scientific Studies, 2025)
The hospitality sector should creatively introduce new products and use the technology to satisfy customer demands. Restaurants are an element of the hospitality industry; restaurants should concentrate on creative services to increase the value of services they offer to customers. Notwithstanding the increasing attention that marketers are paying to customer-perceived innovativeness and customer value co-creation behaviors, little is known about how customer-perceived innovativeness affects customer value co-creation behaviors, customer happiness, and revisit intention. Thus, this research aims to bridge this empirical gap. Data was gathered from 417 customers of quick service restaurants in Riyadh. Data was analyzed by using SPSS 26.0 and partial least squares structural equation modelling (Smart-PLS software, version 4). Results demonstrate that customer-perceived innovativeness positively affects customer value co-creation behaviors, and revisit intention. However, customer perceived innovativeness has no impact on customer happiness. In addition, customer value co-creation behaviors positively affect customer happiness and revisit intention. Furthermore, customer happiness positively impacts revisit intention. This study offers strategic recommendations for real-world practice for businesses that apply creative approaches when adopting customer value co-creation behaviors.